The Interplay Between Family Caring Attitudes, Teacher Caring Behaviour, and Psychological Well-Being Among College Students in China: A Conceptual Framework - Xu, Jirong; Bin Raja Ahmad, Raja Azrul Hisham (South Asian Journal of Social Sciences and Humanities, 2025)
This conceptual paper examines the intricate relationship between family caring attitudes,  teacher caring behaviour, and psychological well-being among college students in China, with  particular attention to the moderating effects of gender and age. Grounded in a comprehensive  review of theoretical frameworks, including Self-Determination Theory, Attachment Theory,  Family Systems Theory, Social Cognitive Theory, Social Communication Theory, and  Noddings' Caring Education Theory. This paper develops a multidimensional conceptual  framework that illuminates how caring dynamics within family and educational environments  collectively influence students' psychological development. The framework conceptualises  family caring attitudes as encompassing emotional support, communication, supportive  environment, and conflict resolution, while teacher caring behaviour comprises emotional  support, teacher-student relationships, academic support, and classroom organisation. These  dimensions are theorised to affect students' psychological well-being across four key domains:  self-acceptance, positive relations with others, environmental mastery, and personal growth.  The paper further explores how these relationships may be moderated by gender and age,  informed by evidence suggesting demographic variations in how students experience and  benefit from caring environments. Formulated in the unique cultural context of Chinese higher  education, this conceptual framework provides a foundation for future empirical research and  the development of targeted interventions to enhance college students' psychological well being through supportive family and educational environments.
Keywords: Family caring attitudes; Teacher caring behaviour; Psychological well-being; Chinese college students; Conceptual framework; Gender differences; Age moderation